Penggunaan Lagu Sebagai Media Pembelajaran Untuk Menumbuhkan Kemampuan Menyimak Di Sekolah Dasar - Posia Mayan Sari (Prodi PGSD Unsultra, 2024)
Listening ability is a basic skill that must be mastered by students in elementary school. However, listening learning is often less interesting for students so that the results are less than optimal. This article is a literature study that aims to explore the use of songs as an effective learning medium in developing students' listening skills. Based on studies from various literatures, songs have the potential to improve students' attention, understanding, and memory. This article examines the theory, benefits, and implementation of songs in listening learning in elementary schools. In addition, challenges and solutions are also presented in using songs as a learning medium.